Osteoid osteoma - M Keupers (Journal of the Belgian Society of Radiology, 2013)
Background: A 12-year-old boy presented with complaints of intermittent left hip pain for over one and a half year. The pain was worse at night and was relieved by taking non-steroidal anti-inflammatory drugs (NSAIDs), such as Aspegic. There was no history of previous trauma. Being a refugee, the patient was lost to follow-up. However, we managed to contact him and arranged a surgical treatment.